EVALUATION OF ANTIDIARRHOEAL ACTIVITY OF ETHANOLIC EXTRACT OF CELTIS TIMORENSIS LEAVES IN EXPERIMENTAL RATS - KUMAR. M, PRASANTH; V, SUBA.; B, RAMIREDDY.; BABU.P, SRINIVAS (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate the antidiarrhoeal activity of ethanolic extract of celtis timorensis leaves. Materials and Methods: The antidiarrhoeal activity of ethanolic extract of Celtis timorensis leaves was investigated by using castor oil induced diarrhoea, castor oil induced enteropooling, charcoal meal test models and atropine was used as a standard reference drug in all the three models. Results: The diarrhoeal severity was reduced significantly (p<0.01) by the extract by 56.85% at 200 mg/kg and 69.48% at 400 mg/kg, whereas 82.12% inhibition was found for the standard drug atropine at dose 3mg/kg. In castor oil induced enteropooling, the extract at doses 200 mg/kg and 400 mg/kg, standard drug atropine showed significant reduction in the volume of the intestinal fluid (p<0.01). In the charcoal meal test, the distance travelled by charcoal meal was significantly reduced by the extract at doses 200 mg/kg and 400 mg/kg (P<0.01) when compared to the castor oil control group. The percent inhibition of charcoal meal was found to be 9.94±1.63 for control group, 15.26±2.11 at 100 mg/kg, 46.81±2.32 at 200 mg/kg, 63.61±2.61 at 400 mg/kg and 75.76±1.72 for standard group. Conclusion: The present findings concluded that the ethanolic extract of celtis timorensis leaves has a significant antidiarrhoeal activity and supports its traditional uses in herbal medicine. Key words: Diarrhoea, Celtis timorensis, Motility, Castor oil, Enteropooling and Charcoal.